Comparative trends of ESG disclosure among Asian countries - Mustafa Kamal, Musmailina; Azmi, Nurul Azlin; Mohamed Yunos, Rahimah; Razi, Nini Suhana Mastini; Abd Sata, Fazrul Hanim (UiTM Cawangan Johor, 2025)
This study examines the trend analysis of Environmental, Social, and Governance (ESG) disclosure among selected Asian countries. This study utilises data from Eikon DataStream, and the final sample comprises 2,848 firm-year observations (2015-2023) across Indonesia, Malaysia, Singapore, and Thailand. The results indicate that ESG disclosure across selected Southeast Asian firms shows a generally positive upward trend, particularly in ENV and SOC pillars, driven by stronger regulations, climate pressures, and rising societal expectations. Meanwhile, GOV disclosure improves more gradually but remains stable. We also found that contributing factors for ESG variations cross-country largely reflect differences in regulatory enforcement and disclosure frameworks. For instance, mandates of Indonesia’s OJK, the introduction of Singapore’s carbon tax and Green Plan 2030, Malaysia’s MCCG reforms, and standardised sustainability reporting in Thailand. These improvement patterns align with stakeholder theory, which highlights firms’ responses to regulatory and societal pressures for legitimacy, and signaling theory, which explains firms’ efforts to reduce information asymmetry and signal credibility and long-term value through enhanced ESG transparency. The study contributes to the body of literature, as limited studies have focused on the factors of ESG disclosure. Prior studies have only focused on the relationship of the study. This study has significant practical implications for investors in overseeing the ESG trend in making investment decisions. This study also helps policymakers improve their ESG regulations for enhanced transparency. This study focuses specifically on investigating the factors behind the ESG trends. The increasing trend after 2019 suggests that stricter ESG disclosure mandates can improve ESG transparency.